Multi-grayscale driving system for a passive-matrix alternating current electroluminescence display with low crosstalk by an asymmetric half-voltage driving strategy - Zhou, Tao; He, Junjie; Yang, Kainian; Shi, Jintao; Chen, Weichun; Zhang, Yue; Peng, Lisha; Zheng, Shaoyong; Chen, Peining; Deng, Shaozhi; Yang, Bo-Ru (Optics letters, 2025)
Alternating current electroluminescence (ACEL) devices have been investigated for their applications in flexible displays, particularly in textile displays. The current driving system for passive-matrix alternating current electroluminescence (PMACEL) still suffers from crosstalk, which significantly affects the display quality. In this study, a circuit model of ACEL is proposed, which is used to simulate the optoelectronic characteristics of ACEL devices as well as the crosstalk of PMACEL by the Simulation Program with Integrated Circuit Emphasis (SPICE). Based on the model, an innovative asymmetric half-voltage driving strategy for PMACEL, featuring lower maximum column signals than the selected row signals and half-amplitude unselected row signals, is developed. This approach effectively mitigates crosstalk by controlling the voltage of unscanned pixels below the threshold voltage of ACEL. Furthermore, a single-pixel ACEL display exhibiting 8 grayscales and a low-crosstalk 8×8 PMACEL display exhibiting 8 grayscales were achieved with this strategy. The results demonstrate the significant potential of the PMACEL display.